PENGARUH INSENTIF DAN KOMPETENSI TERHADAP KINERJA GURU PADA SEKOLAH SMKS NURUL MUTTAQIEN TIGARAKSA - Lilis Nurul H; Yeni Haerani; Syifa Ayu Lestari (JURNAL PENDIDIKAN DAN SAINS, 2022)
This study aims to: analyze the effect of incentives and competencies on teacher performance at the SMKS Nurul Muttaqien Tigaraksa, Tangerang Regency. This research is a quantitative research. The population of this study were teachers of SMKS Nurul Muttaqien Tigaraksa, Tangerang Regency, amounting to 30 people. All members of the population were sampled in this study (saturated sample). The results of the research on the independent variable incentive X1 obtained t count (2,995) > T table ( 1,701 ) and the competence variable X2 t count (2,225) > t table (1,701). So, the incentive variable (X1) has a partial effect on the teacher's performance variable (Y), and the competence variable (X2) has a partial effect on the teacher's performance (Y). The f test results show that f count (29.892) > f table (1.703). With a significance of 0.000 < alpha = 0.000 < 0.05, then Ho is rejected and Ha is accepted. The test results of the coefficient of determination (R2) show Adjusted R Square of 0.777, it can be concluded that the Incentive and Competency variables affect the teacher performance variable by 77.7% while the remaining (100-77.7%) = 22.3% is influenced by other factors .